Integrating genetic control tools for insect pest and insecticide resistance management - Brewer, T (2022)
Pest insects that attack crops and vector disease continue to impose a tremendous burden on both global agricultural production and public health. Insecticidal interventions have greatly enhanced the control of pest insect populations, but their continued efficacy is threatened by the evolution of resistance. Developing novel tools and strategies to manage resistance to insecticides and strengthen population suppression will be essential for our continued ability to mitigate the impact of pest insects on human populations. Releases of insects genetically modified to possess a self-limiting, lethal transgene that conditionally terminates female offspring during development are a novel, species-specific tool that could be used alongside insecticidal interventions to manage resistance and enhance population suppression. However, while their potential as a pest suppression tool has been well characterised, more work is required to expand our understanding of their potential for resistance management. Using a spatially-explicit population dynamics and genetics model, I first evaluate the efficacy of landscape-level strategies combining the planting of refuge crops with self-limiting releases for the control of an agricultural pest and its resistance to insecticidal crops. I show that replacing area-wide releases with releases targeted at population hotspots can provide effective landscape level population suppression and resistance management. I also demonstrate that reinforcing insecticidal crops with releases can compensate for violations of existing resistance management practices to maintain population and resistance control. I then expand considerations of these integrated strategies from agriculture to public health, investigating whether self-limiting releases can be deployed alongside insecticidal nets (LLINs) and indoor residual sprays (IRS). I present a population demographic and genetic model capable of simulating the response of a sex-, stage-, and genotype-structured anopheline population with overlapping generations to control strategies integrating pulsed releases of self-limiting insects with bed nets or indoor sprays. Using this model, I then investigate how resistance evolution and behavioural avoidance, recognised as current threats to the continued efficacy of nets and sprays, erode insecticide-only control. Finally, I demonstrate that plausible release strategies could reinforce population and resistance management to delay or reverse the evolution of resistance, and compensate for the reduced exposure to nets and sprays induced by behavioural avoidance.